2012
DOI: 10.4236/ojmn.2012.23008
|View full text |Cite
|
Sign up to set email alerts
|

The Haematological Profile of Patients with Multiple Sclerosis

Abstract: Background: Patients with multiple sclerosis experience various disabilities, depending on the number and placement of lesions in the brain. Red blood cells with impaired membrane fluidity, as has been reported in patients with multiple sclerosis are known to be further targeted by phospholipase A2 during inflammatory activation. Objectives: The objective of the present study was therefore to investigate the haematological profile of patients with multiple sclerosis and to correlate this with their functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(59 reference statements)
3
11
0
3
Order By: Relevance
“…The two studies above are in agreement with our results related to the highly significant increasing in HbA 1c level in patients with multiple sclerosis (without treatment) in comparison with healthy control, Table ( 1). Moreover, it has been reported that patients with multiple sclerosis experience various complications, depending on the number of locations of lesions in the brain, erythrocytes with impaired membrane fluidity as shown in multiple sclerotic patients [27]. Furthermore, a recent study has suggested that iron is an essential element used for basic and specialized cellular functions throughout the body and in the central nervous system [28].…”
Section: Discussionsupporting
confidence: 92%
“…The two studies above are in agreement with our results related to the highly significant increasing in HbA 1c level in patients with multiple sclerosis (without treatment) in comparison with healthy control, Table ( 1). Moreover, it has been reported that patients with multiple sclerosis experience various complications, depending on the number of locations of lesions in the brain, erythrocytes with impaired membrane fluidity as shown in multiple sclerotic patients [27]. Furthermore, a recent study has suggested that iron is an essential element used for basic and specialized cellular functions throughout the body and in the central nervous system [28].…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicate trustable data, since MS patients with earlier age of onset have a milder MS course, while a continuing disease process in the long-term deteriorates the clinical condition and increases MSSS 19. Our data, discussed later, are also congruent with previous findings, which showed inverse correlation between the RBC counts and EDSS in MS patients 6. In this current investigation, the two most statistically significant findings were that higher HbA2 levels correlated with higher RBC levels ( R =0.357, P <0.001) and prominently lesser MSSS ( P <0.001).…”
Section: Discussionsupporting
confidence: 92%
“…These observations were neglected until the past few years and no one questioned the influence of RBC fragility and free hemoglobin (Hb) in MS. But this has changed in recent years 26. In 2009, an impaired fluidity of RBC membranes in MS was reported 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 The hematological profile of patients with MS indicates an increased number of platelets in the circulation of patients, which may suggest their immunological involvement. 52 Therefore, the decrease in platelet count in MS patients may be a positive force for protecting against the development of the disease. Farrokhi et al showed a statistically significant decrease in platelet level for patients taking fingolimod oral medication (reducing classic autoimmune cells).…”
Section: Role Of Blood Platelets In Neuro-inflammation and Neurodegenmentioning
confidence: 99%